Artificial intelligence with scratch programming - Toha, Siti Fauziah; Ibrahim, Azhar Mohd; Azmi, Nur Liyana; Abu Hanifah, Rabiatuladawiah; Abdul Malik, Muhammad Hafizi; Mohd Romlay, Muhammad Rabani (Centre for the Professional Development (CPD), IIUM, 2021)
The purpose of this book is to provide a general understanding of Artificial Intelligence (AI) or Kecerdasan Buatan. Readers will discover and explore the uses and applications of AI, understand AI concepts and terms such as the training, testing process as well as analyzing the predictive impact of modelling and optimization accuracy. Readers will be exposed to the 1) History of the development of Artificial Intelligence and the 2) Benefits of learning AI which is in line with the boom of the 4.0 industry revolution. Artificial intelligence technology is one of the branches of science in making a system that could have the human-like intelligence ability. It has great potential in automating operations and work that are repetitive in nature. The use of AI technology is very important in solving complex tasks to save time and manpower. Among the important branches of AI is ‘machine learning’ and further the annotation of ‘deep learning’ intertwined which is the ability of machines that are able to 'learn' to be smart. Conceptually, the machine that will be 'taught' by humans needs to be equipped with a lot of information to make it smarter than other machines. In other words, the machine will be equipped with thousands of attempts to complete a task. Throughout this process, the machine will understand and learn concepts to complete the task in improvise in each cycle. This book requires no programming or computer science expertise and is designed to introduce the basics of AI to anyone whether you have a technical background or not.